SEMINAR DAN PELATIHAN PENULISAN PROPOSAL PTKBK BAGI MAHASISWA BIMBINGAN DAN KONSELING FKIP UNCEN - Habel Saud; Yansen Alberth Reba (LP4MK STKIP PGRI Lubuklinggau, 2021)
The objectives of the present study are to: 1) find knowledge and understanding of the concept of CAR related to guidance and counseling, 2) define professional competencies that support profession as a prospective counselor/professional counseling teacher, 3) systematically and scientifically understand the stages of classroom action research related to guidance and counselling. The research activities apply the lecture, discussion/question and answer method, and training in writing class action research proposals related to guidance and counseling. Seminars and training for writing class action research proposals related to guidance and counseling involve guidance and counseling students in semesters 4, 6 and 8 of Guidance and Counseling Program of FKIP UNCEN. The results of the study found that students who answered ‘strongly agree’ were 22.86% and those who answered ‘agree’ were 77.14%. In conclusion, all students who attend seminars and training in writing CAR proposals related to guidance and counseling can understand and comprehend well the importance and benefits of CAR related to BK material for prospective guidance and counseling teachers in schools.